Self-compating concrete reinforced with tyre recycled fibres - Christofe, Andreas; Neocleous, Kyriacos; Polydorou, Thomaida; Kkolos, Andreas; Hadjimitsis, Diofantos G. (My University, 2017)
An experimental study is presented on the development of steel fibre-reinforced concrete mixes, that are suitable for thin overlays in new and damaged concrete surfaces. To minimise the effort required for casting and compacting, the study aimed at developing concrete mixes that can be classified as self-compacting. Thus, a range of fresh concrete properties were examined to assess the workability of these mixes; the compressive and flexural strength was also examined experimentally. In total, six mixes were examined including a plain concrete mix; five types of short steel fibres were trialled: Recycled Tyre Steel Fibres with a dominant length range of 5 to 15 mm, and four types of Tyre Steel Cord Filaments, each type cut to a specific length. Three fibre contents were trialled (25, 50 and 100 kg of fibres per m3 of concrete), but preliminary results indicated that the self-compacting properties (i.e. filling and passing ability, viscosity as well as segregation resistance) are diversely affected for concrete mixes with fibre contents greater than 25 kg/m3. The main conclusion of this study was that screed mixes containing short Tyre Steel Cord Filaments can be classified as self-compacting. While, the mix containing Recycled Tyre Steel Fibres did not fulfil the acceptance criteria set for passing ability. However, this does not imply that this fibre type should not be used in fibre-reinforced overlays of concrete surfaces, since conventional rebars are not expected to be used in such applications and, thus, passing ability is not considered crucial for this type of application. The bending test results indicated that the longer Tyre Steel Cord Filaments as well as the Recycled Tyre Steel Fibres are effective in providing crack bridging at high crack-openings.
Keywords: Recycled steel fibres; Screeds; Self-compacting concrete; End-of-Life tyres